Arthritis, comorbidities, and care utilization in veterans of operations enduring and Iraqi Freedom. Issue 3 (20th June 2016) - Rivera, Jessica C.; Amuan, Megan E.; Morris, Ruth M.; Johnson, Anthony E.; Pugh, Mary Jo
ABSTRACT: Veteran populations are known to have frequencies of arthritis higher than civilian populations. The aim of this study is to define the prevalence of arthritis among a cohort of veterans from ongoing U.S. military operations. A retrospective cohort study using Veterans Administration data sources for service connected disability, comorbidities, clinic utilization, and pharmacy utilization was conducted including veterans who deployed in service to operations in Afghanistan or Iraq, comparing veterans with a diagnosis of arthritis, arthritis plus back pain, and veterans with no pain diagnoses. The frequency of arthritis was 11.8%. Veterans with arthritis and arthritis plus back pain had greater frequencies of diabetes, hyperlipidemia, hypertension, and obesity compare to veterans with no pain diagnosis. Veterans with arthritis plus back pain had the highest pain clinic utilization and prescription use of opioids and anti‐inflammatories. Veterans with no pain diagnosis had higher frequencies of diagnosis and clinic utilization for mental health disorders. Arthritis is prevalent among the latest generation of combat veterans and is associated with diabetes, obesity, and cardiovascular comorbidities. The need for arthritis care and associated comorbidities is expected to increase as the Veterans Administration and the civilian health care sector assumes care of these veterans. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:682–687, 2017.